“Aplicación de las metodologías de observación directa e indirecta en el monitoreo del zorro andino (lycalopex culpaeus reissii), para determinar su presencia en la parroquia 11 de Noviembre” - Chávez Mejía, Cristina Belén (2023)
The loss of the Andean fox has a negative influence on the biological balance of ecosystems, as it is a bioindicator of environmental quality, as a controller of the balance of other species living in the same habitat. Therefore, it is necessary to estimate the presence of foxes in different areas of Ecuador. Consequently, the objective of this research was to apply methodologies of direct observation (transects) and indirect observation (feces, burrows, tracks, hair and bones) in order to determine the presence of the Andean fox (Lycalopex culpaeus reissii) in the parish of 11 de Noviembre. This species is important in the ecosystem because of its role as a predator in the food chain, its influence in the regulation of prey populations and that in Ecuador it is categorized as being of minor importance. The application of direct observation methodology was carried out with the application of three transects with a dimension of 20m x 30m, formed by 6 quadrants of 10m x 10m, which were used for the application of the indirect observation methodology that corresponds to the collection of evidence such as: footprints, feces, tracks, bone, hair and other signs of presence in the parish. In conclusion, no evidence of the presence of the Andean fox (Lycalopex culpaeus reissii) was obtained. In spite of the efforts made in the surveys, the application of transects and the identification of tracks, footprints and other signs, no data were obtained to confirm the existence of this species in the study area, due to the anthropogenic activities that occurred in the area and even the testimonies of residents who claim that they have never found it despite living in this parish for more than 50 years.